MANAJEMEN PERBAIKAN KUALITAS DENGAN METODE DMAIC PADA PROSES MACHINING PRODUK VS - Anni Intan Faricha; Yugowati Praharsi; Farizi Rachman (Program Studi D4-Manajemen Bisnis, Jurusan Teknik Bangunan Kapal, Politeknik Perkapalan Negeri Surabaya, 2023)
Quality Management is one of the activities of a foundry manufacturing company in order to develop and continue to manage the business processes in it. One of the VS casting products has a production period of 1 month from the injection moulding process to the machining stage using CNC lathe and milling. In quantity, many products have quality levels that are not up to standard. Based on data from the beginning of the year in February 2023, observations were made for 1 month to recap the production results in the finishing department of the machining section. It was recorded that there were 40% defective products out of a total of 686 pcs. After making improvements using the DMAIC method, the finished good machining target has increased to 52%. Coupled with the help of Minitab statistical software in calculating the sigma value from 2.09 can change to 2.2 with an initial DPMO of 275,520 down to 261,662. The calculation is also equipped with a cause analysis using the 4M + 1E factor and the implementation of improvements to each cause. The writing of this paper also provides advice on using form control to anticipate the loss of quality in VS products.